Non-Muslim Voices on Halal Certification: From Sectoral-Religious Tendencies to State-Mandated Regulations - B.J. Sujibto; Fakhruddin M (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
In recent years, halal food and products have been expanding into the global economy, and today's halal market is estimated around USD 2.4 trillion globally. This article discusses the understanding and articulation of halalness and halal certification among non-Muslim business communities in Indonesia, focusing on owners of small and medium enterprises (SMEs). Their voices need to be heard and responded to, especially by government agencies. Since the non- Muslim communities’ understanding of halalness is mostly based on their life experiences, it could be treated as empirical data to inform policy-making. Meanwhile, the government has issued Halal Product Assurance (JPH) Law 33/2014, which mandated the establishment of the Halal Product Assurance Organizing Agency (BPJPH). The enforcement of JPH Law is an attempt to strengthen the BPJPH’s position, but it faces challenges and conflicts of interest in politics and business. Using a qualitative approach to collect data from non-Muslim SME business players in Yogyakarta and Semarang, this study found that the articulation and understanding of halalness are narrowly sectoral, religious, and ideological. Rather than halal certification, the Indonesian Food and Drug Authority (BPOM) has become a more trusted certification. Therefore, the presence of the state is needed to regulate and optimize the fundamental aspects of halal certification, such as hygiene, cleanliness, and health.